Portfolio Rebalancing in Japan : Constraints and Implications for Quantitative Easing - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2015)
Portfolio rebalancing is a key transmission channel of quantitative easing in Japan. We construct a realistic rebalancing scenario, which suggests that the BoJ may need to taper its JGB purchases in 2017 or 2018, given collateral needs of banks, asset-liability management constraints of insurers, and announced asset allocation targets of major pension funds. Nonetheless, the BoJ could deliver continued monetary stimulus by extending the maturity of its JGB purchases or by scaling up private asset purchases. We quantify the impact of rebalancing on capital outflows and discuss JGB market signals that can be indicative of limits being within reach.